Optimalisasi Turbin Angin Savonius Vertikal Berbasis MPPT Algoritma Perturb and Observe (P&O) sebagai Suplai Sistem Pemanas Air di Kapal - Aryo Dwi Pinanggola; Henna Nurdiansari; Maulidiah Rahmawati (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
As an archipelagic country, Indonesia has significant potential for the utilization of renewable energy, particularly wind energy in maritime areas with low wind speeds (3–6 m/s). This study aims to design and test a vertical Savonius wind turbine system equipped with a Perturb and Observe (P&O) Maximum Power Point Tracking (MPPT) algorithm as a power source for shipboard water heating systems. The research method applied is Research and Development (R&D), integrating several components such as a DC generator, full-wave bridge rectifier, INA219 current sensor, anemometer cup sensor, ESP32 microcontroller, and a monitoring interface utilizing Google Spreadsheet and a 20x4 LCD. The system was tested under two operating conditions: without MPPT and with MPPT. The experimental results show that the application of the MPPT algorithm successfully increased power output by up to 272.64% while maintaining voltage stability despite varying wind speeds. Nevertheless, the average output power of 2.605 W remained insufficient to meet water heating requirements within a short time. For example, charging a 12V 50Ah battery would require approximately 9.6 consecutive days of operation, highlighting the system’s limitations in high-demand scenarios. Despite these constraints, the findings demonstrate that the vertical Savonius wind turbine integrated with MPPT has strong potential as a clean and environmentally friendly alternative energy solution for maritime applications, particularly for small-scale onboard electrical loads. This study contributes to renewable energy utilization in the shipping sector and provides a foundation for further technological development and optimization.